GURU MUGHNI KUNINGAN (1860-1935) - Helmi Hidayat (Al Qalam, 2012)
There has been a strong linkage between the dissemination of Betawi culture and Islam in Jakarta. The prominent figures of Betawi are generally known as "kyai" or religious leaders. The Indonesian history recorded that Betawi people were strictly fanatic Muslims and, to some extent, during the Dutch colonization era they were strongly well-known as anti-Western. They tended to identify Western people as infidels. Nevertheless, the portrait of Islam and the social history of Muslim intellectuals among Betawi have not been much scrutinized. The researchers just gave more attention dealing with the social history, politics, arts and culture, and archeology of Betawi. This article tries to give contribution to the development of what Azra called biographical dictionary as a part of the tarajim ulama literature. Key Words: Abdul Mughni, Ulama, Betawi, Islam, Bibliographical Dictionary